PENYUSUNAN LAPORAN KEUANGAN WAJIB PAJAK UMKM BERBASIS SAK EMKM SEBAGAI DASAR PELAPORAN SPT TAHUNAN - Firmansyah, Firmansyah; Layli, Meutia (Jurnal Berdaya Mandiri, 2023)
Preparation of financial reports for MSME taxpayers on the basis of SAK EMKM which is the basis for reporting Annual Tax Returns (SPT). This community service activity aims to provide socialization to taxpayers regarding the preparation of SAK-based financial reports and hopes to be able to provide understanding and knowledge regarding this matter. This is the basis for holding this service activity with the hope that the understanding and knowledge that has been received by MSME taxpayers can be applied by reporting their annual SPT correctly, clearly, completely, and on time. Participants in this socialization activity were MSMEs in the city of Samarinda and students at Widya Mahakam Samarinda University. This activity was carried out in three stages, namely identifying, delivering material, as well as discussion and solutions. This dedication becomes useful knowledge so that you can practice how to prepare and report your taxes with SAK UMKM based reports. Keywords: Accounting, SAK EMKM, Tax